Transcriptomic profile of epileptic children treated with ketogenic therapies - Jana Ruiz-Herrero; Gloria Olaso-Gonzalez; Eva Serna; Elvira Cañedo-Villarroya; Angela G. Correas; Juan Gambini; Mari Carmen Gomez-Cabrera; Consuelo Pedrón-Giner; Jose Vina (Journal of Integrative Neuroscience, 2022)
Background: Ketogenic dietary therapies (KDT) are used as a treatment in childhood epilepsy. However, their mechanism has not yet been established. The main objective of this study was to determine the changes in the transcriptomic profile induced by KDT in children with epilepsy in order to shed light on its possible mechanisms. Methods: Eight children with refractory epilepsy were enrolled in the study. Peripheral blood mononuclear cells were obtained before and after the children were treated with KDT for a minimum of 6 months. RNA was extracted and mRNA and miRNA profiling were performed and analyzed. Results: Our intervention with KDT significantly reduced the seizure number in seven of the eight paediatric patients treated and caused important changes in their gene expression profile. Our study reveals modifications in the transcription of 4630 genes and 230 miRNAs. We found that the genes involved in the protection against epileptic crises were among those mainly changed. These genes collectively encode for ion channels, neurotransmitter receptors, and synapse structural proteins. Conclusions: Together our results explain the possible mechanisms of KDT and reinforce its clinical importance in the treatment of epilepsy.